The Influence of Service Marketing Mix and Umrah Service Quality on Customer Satisfaction and Customer Loyalty towards Umrah Travel Agents in Malaysia - Othman, Bestoon; Harun, Amran Bin (Technium Social Sciences Journal, 2021)
In the Malaysian Umrah industry, there are so many new participants selling and offering similar products and services. As a result, Umrah providers must compete to survive in this industry, as there are currently so many competitors. They need to focus on customers’ special needs and preferences to maintain and retain the long-term relationship. Thus, the objective of this study is to examine the relationship between service marketing mix and Umrah service quality on customer loyalty towards Umrah travel agents, and the mediating effect of customer satisfaction in the relationship between service marketing mix/service quality and customer loyalty towards Umrah travel agents in Malaysia. This study explored and integrated two new dimensions (not Ps) for service marketing mix namely after-sale service and marketing communication rather than traditional service marketing mix of 7 P’s. The study’s research framework was supported by the Stimulus-Organism-Response theory. Three of the four main constructs namely; service marketing mix, Umrah service quality and customer satisfaction were conceptualised as second order constructs and assessed via the reflective-formative approach. Customer loyalty which acted as the dependent variable was measured reflectively through seven multi items. All the items were assessed using the 5-point Likert scale. Data was derived from 384 Umrah customers who have used Umrah traveling services. All the constructs such as product, price, promotion, place, people, process, physical evidence, marketing communication, and after-sale service (marketing mix), Umrah service quality includes tangibles, reliability, responsiveness, assurance, and empathy had significant effects on customer satisfaction and customer loyalty. However, second hypothesis Umrah service quality and customer loyalty which were found not significant. Two indirect effect hypotheses to examine the role of customer satisfaction as mediators were accepted as full mediation. The study findings were discussed thoroughly and concluded with a discussion on the implications, the limitation of the study and recommendations for future study.